Use of E - learning as a Learning Method Among Students - Sirait, Steven; Anjelita; Tantia, Nia (Cattleya Darmaya Fortuna, 2024)
This study investigates the utilization of e-learning as a prevalent learning method among students. With the proliferation of digital technology, e-learning has become increasingly popular as an alternative or complement to traditional classroom-based instruction. Through a comprehensive literature review, this research explores the various factors driving the adoption of e-learning among students, including flexibility in scheduling, accessibility to resources, and personalized learning experiences. Additionally, the study examines the challenges associated with e-learning implementation, such as digital literacy barriers, technological infrastructure constraints, and concerns regarding social interaction and engagement. Furthermore, the research evaluates the effectiveness of e-learning in facilitating knowledge acquisition, skill development, and academic achievement compared to traditional learning methods. By synthesizing empirical evidence and case studies, this study aims to provide insights into the evolving landscape of e-learning and its implications for educational practice and policy. The findings contribute to a deeper understanding of the opportunities and challenges associated with the widespread adoption of e-learning as a learning method among students in contemporary education systems.